Teacher training pathway to work in distance education - Morais , Ione Rodrigues Diniz; Zaros , Lilian Giotto; Garcia , Tânia Cristina Meira; Rêgo , Maria Carmem Freire Diógenes (Seven Editora, 2023)
To support the teaching practice in distance education, it is necessary for the teacher to acquire and/or improve didactic, pedagogical and digital skills. Thus, the objective of the present work is to describe the design of the Teacher Training on Distance Education course considering the objectives, the modular structure, the content topics, the methodology and the evaluation process. This course was structured in three modules: 1- Conceptual contributions and institutional and pedagogical design of distance education at UFRN; 2- Didactic-pedagogical organization of the teaching action; 3- The Mandacaru Moodle as a space for teaching action: from tools to methodological approaches. The modules were taught synchronously through Google Meet, lasting 3 hours each and on 3 consecutive days. At the end of the synchronous stage, the teachers participated in the asynchronous moments for 30 days. In the virtual learning environment, complementary bibliographies and communication forums were made available so that the participants could answer questions after the synchronous stage. The process of evaluating teacher training was procedural, considering the course participant's participation in the forums, the nature of the questions formulated by him and the feedback obtained at the end of the course in terms of evaluation regarding the content, methodology and training contributions to the teaching performance in distance education. DOI:https://doi.org/10.56238/ptoketheeducati-070